PERUBAHAN HISTOPATOLOGI AORTA AKIBAT PAPARAN ASAP KEBAKARAN BIOMASSA GAMBUT PADA MODEL MENCIT (Mus musculus) - May Valzon; Widya Rizkika Islami (Collaborative Medical Journal, 2023)
Indonesia is one of the countries that often experiences large-scale forest and peatland fires. The biggest disaster after the tsunami that occurred in Indonesia has occurred since the last dozen years, especially in Riau, Kalimantan. The smoke produced from these forest fires can worsen the air which will be inhaled and entered through the lungs so that it can enter the blood vessels and circulate throughout the body. It gives a direct effect by some of the components contained in the particles, such as endothelial damage to blood vessels due to particulate matter. Short-term exposure will cause acute atherothrombosis, ischemia, regulation of the inflammatory response as well as a decrease in blood vessel diameter. Meanwhile, long-term effects will occur such as local inflammation to atherogenesis. This study aims to analyze changes in the diameter of the aortic lumen and the presence or absence of endothelial foam cells. using a true experimental study with a posttest approach with control group on 6 mice that received exposure to fire smoke, 6 mice that did not get exposure or as a control for 10 days. Based on Fisher's test, it was found that exposure to peat burning smoke for 10 days caused the formation of foam cells on the aortic wall.